2022
DOI: 10.3389/fimmu.2022.836494
|View full text |Cite
|
Sign up to set email alerts
|

CB2R Activation Regulates TFEB-Mediated Autophagy and Affects Lipid Metabolism and Inflammation of Astrocytes in POCD

Abstract: Evidence suggests that the accumulation of lipid drots (LDs) accelerates damage to mitochondria and increases the release of inflammatory factors. These have been implicated as a mechanism underlying neurodegenerative diseases or tumors and aging-related diseases such as postoperative cognitive dysfunction (POCD), nevertheless, accumulation of lipid droplets has not been extensively studied in the central nervous system (CNS). Here, we found that after surgery, there was activation of astrocytes and lipid accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 61 publications
0
27
0
Order By: Relevance
“…Moreover, oxidative stress and mitochondrial damage are essential links in the pathogenesis of POCD [ 11 ]. Furthermore, a considerably large number of research works have revealed that although the causes of neurocognitive disorders are different, there are some similar pathological injury mechanisms in these diseases, such as mitochondrial damage, excessive ROS production, nervous system inflammation, and so on [ 12 , 13 ]. Studies have confirmed that abnormal mitochondrial dynamics is an early sign of neurocognitive disorders [ 14 ], which happens before the amyloid beta protein aggregation, phosphorylation of Tau protein, and neuronal apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, oxidative stress and mitochondrial damage are essential links in the pathogenesis of POCD [ 11 ]. Furthermore, a considerably large number of research works have revealed that although the causes of neurocognitive disorders are different, there are some similar pathological injury mechanisms in these diseases, such as mitochondrial damage, excessive ROS production, nervous system inflammation, and so on [ 12 , 13 ]. Studies have confirmed that abnormal mitochondrial dynamics is an early sign of neurocognitive disorders [ 14 ], which happens before the amyloid beta protein aggregation, phosphorylation of Tau protein, and neuronal apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Although the precise pathogenesis of POCD is still unclear, several investigations have veri ed that in ammatory cytokines-related mechanisms are involved in critical roles in the development and regression of POCD [8][9]19]. As immune effector cells intrinsic to the central nervous system, microglia are known to mediate CNS in ammation mediated [20].…”
Section: Discussionmentioning
confidence: 99%
“…Although the speci c pathogenesis of POCD is unclear, numerous investigations have con rmed that in ammation plays a critical role in the progression and development of POCD [8][9]. As a classical in ammatory pathway, TLR4/NF-κB has received growing interest in the study of POCD [10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Massive bleeding, a strong stress response and an inflammatory response are the main complications of lumbar spine surgery, and these may be the root cause of POCD, so it is necessary to intervene in this type of surgery in advance to minimize the occurrence of such complications. Although it is still uncertain whether the inflammatory response is the underlying cause of POCD, the levels of inflammatory factors in peripheral blood ( Zhang et al, 2022 ), the integrity of the BBB ( Cao et al, 2018 ), and the activation of astrocytes and microglia ( Li et al, 2020 ) appear to play an important role in the pathogenesis of POCD.…”
Section: Discussionmentioning
confidence: 99%